Como tentar (se) esconder d(o) tempo: um estudo sobre as potencialidades da imagem latente - Icaro Moreno Ramos (2019)
The work that unfolds in the next pages is an attempt to answer the questions I have casted through one of my works: the one in which I am soldering a 6x7 camera to seal inside it 10 images made to never be seen the images of my father shortly before his death, on a hospital bed. Faced with this gesture, among many questions, there is one that comes to exist and to resist as a leitmotiv: are there images in the field of the arts, that are made not to be visualized? As the images of my dyingfather, is there a set of images that are somehow guarded from being seen? Starting from these images that were made invisible, we will try to think of seeing as an act divide from the beginning, using, for this, a conceptual set obtained mainly from thinkers such as Georges Didi-Huberman, Maurice Merleau-Ponty, Jacques Derrida and Walter Benjamin. And since even images without manifestation inevitably have an apparatus of visual functioning to cover them up, we will talkabout the furtive and also constituent game of its underneaths. Among these images, the undeveloped photograph, known as latent image, will hold a prominent place, especially at times when it will no longer be considered as a mere condition of the photographic praxis so that one may act as a poetic strategy. We will convene, in order to enrich this issue, the work of artists such as Robert Barry, ChimPom, Alfredo Jaar, Pierre Huyghe, Jochen Gerz, Doris Salcedo, Christine Koslov, Oscar Molina and Lorena Guillén Vaschetti (among others). My own plastic work and creative process will also be present in the research, either throughan artistic praxis in which the knowledge brought by the theoretical reflections is applied, or through an analytical reflection that feeds back to the works themselves.